IMPLEMENTASI METODE ROLE PLAYING MATERI PEMULASARAN JENAZAH : (Studi Analisis Deskriptif di Kelas XII Putri Pondok Pesantren Nurus Sunnah Kota Tegal) - Sri Rahayu; Koko Khoerudin (Berajah Journal, 2025)
This study aims to explore the implementation of the role-playing method in Fiqh teaching and its implications for Grade XII students’ understanding of mortuary rites (pemusalaran jenazah) at Nurussunnah Islamic Boarding School, Tegal. The research employs a qualitative descriptive approach. Data were collected through observation, interviews with teachers and students, and documentation of the learning process. The findings reveal that the role-playing method is implemented in three phases: scenario preparation, role enactment by students, and post-simulation reflection. Through this method, students become more active, enthusiastic, and able to practically grasp the procedural steps of mortuary rites, including washing, shrouding, performing the funeral prayer, and burial. Furthermore, the method significantly enhances both the students’ conceptual understanding and practical skills. Therefore, role-playing is recommended as an effective instructional strategy in Fiqh education, especially for procedural topics such as mortuary rites.